Transportation Cyber-Physical Systems - Deka, Lipika; Chowdhury, Mashrur A. (Elsevier, 2018)
"Transportation Cyber-Physical Systems provides current and future researchers, developers and practitioners with the latest thinking on the emerging interdisciplinary field of Transportation Cyber Physical Systems (TCPS). The book focuses on enhancing efficiency, reducing environmental stress, and meeting societal demands across the continually growing air, water and land transportation needs of both people and goods. Users will find a valuable resource that helps accelerate the research and development of transportation and mobility CPS-driven innovation for the security, reliability and stability of society at-large. The book integrates ideas from Transport and CPS experts and visionaries, consolidating the latest thinking on the topic. As cars, traffic lights and the built environment are becoming connected and augmented with embedded intelligence, it is important to understand how smart ecosystems that encompass hardware, software, and physical components can help sense the changing state of the real world. Bridges the gap between the transportation, CPS and civil engineering communities. Includes numerous examples of practical applications that show how diverse technologies and topics are integrated in practice. Examines timely, state-of-the-art topics, such as big data analytics, privacy, cybersecurity and smart cities. Shows how TCPS can be developed and deployed, along with its associated challenges. Includes pedagogical aids, such as Illustrations of application scenarios, architecture details, tables describing available methods and tools, chapter objectives, and a glossary. Contains international contributions from academia, government and industry"--